2014
DOI: 10.14740/jem211w
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of a Composite Pheochromocytoma With Neuroblastoma

Abstract: Composite pheochromocytoma (CP) is a rare tumor of the adrenal medulla, consisting of neuroendocrine and neural components. Despite similar neural crest origins, pheochromocytomas and neurogenic tumors are distinct entities. Symptoms may arise from hypersecretion of hormones by either component; however, not all patients present with classic symptoms. Moreover, various medical conditions and substances can confound screening tests and complicate the diagnosis. The patient, a 46-year-old male, was seen in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Tumors with morphologic features of pheochromocytoma and stroma-poor neuroblastoma in the same lesion are rare and are commonly referred to as “composite pheochromocytoma.” Table 1 summarizes the clinical features of published cases [ 2 – 7 ]. We report two additional cases for which we provide further molecular characterization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumors with morphologic features of pheochromocytoma and stroma-poor neuroblastoma in the same lesion are rare and are commonly referred to as “composite pheochromocytoma.” Table 1 summarizes the clinical features of published cases [ 2 – 7 ]. We report two additional cases for which we provide further molecular characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Case 3 represents an outlier, since this 38-year-old patient died with widely metastatic disease within 3 months of diagnosis. With the exception of the case reported by Comstock et al which demonstrated no N-MYC gene amplification in the tumor of their NF1 patient [ 6 ], other studies did not investigate this important prognostic factor [ 2 – 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Composite pheochromocytoma refers to tumors with morphologic features of PCC and NCC‐derived tumors, such as malignant peripheral nerve sheath tumor and neuroendocrine carcinomas, within the same tumor 4,5 . Composite tumors are rare and most often combined with ganglioneuroma in composite PCC; therefore, composite tumors comprising PCC and NB are even rarer 5‐10 . The genetic mechanism of composite tumors with PCC and NB remains unclear; a single nucleotide polymorphism array analyzed only 1 case 5 .…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 Composite tumors are rare and most often combined with ganglioneuroma in composite PCC; therefore, composite tumors comprising PCC and NB are even rarer. 5 , 6 , 7 , 8 , 9 , 10 The genetic mechanism of composite tumors with PCC and NB remains unclear; a single nucleotide polymorphism array analyzed only 1 case. 5 Here, we applied exome and transcriptome analyses to a patient case with a composite tumor with NB and PCC to investigate whether the NB and PCC lesions arose from a common cellular origin and how this tumor developed.…”
Section: Introductionmentioning
confidence: 99%